Maternal Oxygen Administration as an Intrauterine Resuscitation Measure During Labor. Issue 2 (March 2015) - Simpson, Kathleen Rice
<x xml:space="preserve">Abstract</x> What is the role of maternal oxygen administration for intrauterine resuscitation during labor when the fetal heart rate pattern is indeterminate (category II) or abnormal (category III)?